Removal of Methyl Orange Using Nanocomposites Based on Polyaniline/Nb2O5/MnO2 and Polyaniline/Nb2O5/Cr2O3 as New Adsorbents - Karrar Majeed Obaid; Ahmed Saadoon Abbas; Yahya Fahim Al-Khafaji (Universitas Gadjah Mada, 2023)
Dyes are the most widely employed materials for coloring applications, especially for industrial purposes; thus, dyes are applied in the textile, cosmetics and foodstuffs. Dyes are very important owing to their applications in all aspects of human life. Accordingly, the production volume of dyes around the world is increasing. In this study, a new type of multifunctional material: polyaniline/Nb2O5/MnO2 and polyaniline/Nb2O5/Cr2O3 nanocomposites, was prepared by chemical polymerization from aniline monomer in the presence of metal oxides (Nb2O5, Cr2O3, and MnO2) and an oxidant (ammonium persulfate) in acidic aqueous solution for the elimination of dye from water. Herein, the nanocomposite was found to be a favorable adsorbent for wastewater treatment due to its high adsorption and efficiency, self-regeneration quality, low cost and easy synthesis. Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy and UV-visible spectroscopy were used to assess the synthesized nanocomposites' characteristics. From the results, we discovered that polyaniline nanocomposites doped with Nb2O5 and MnO2 nanoparticles had a higher adsorption efficiency ( 97.37%) than those found in polyaniline with Cr2O3 and MnO2 ( 94.3%). We looked at the adsorption conditions, including the medium's pH, the initial dye concentration, the dosage of the adsorbent, and the adsorption time.